Failure points in the PKI architecture - Prodanović, Radomir I.; Vulić, Ivan B. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Over the last 20 years, the PKI architecture has found its vast application, especially in the fields which require the establishment of a security infrastructure. Given that the purpose of this architecture is to be used for achieving higher security standards, its smooth operation has to be one of the main requirements for its implementation. Its complexity is mirrored in the numerous implementations that the PKI has had so far. For all the reasons mentioned above, it is of great importance to consider potential failure points of such a structure. Due to the complexity of these structures, this paper will present only a basic review of such stress points, without providing details on specific applications and types of implementations. The significance of failure points will be explained by examining the common features of the PKI architectures and the occurrence of failure points in these structures, and where possible, an overview of suggestions for preventing such failures will be provided.